Is virtual reality the solution? A comparison between 3D and 2D creative sketching tools in the early design process - Houzangbe, Samory; Masson, Dimitri; Fleury, Sylvain; Gómez Jáuregui, David Antonio; Legardeur, Jeremy; Richir, Simon; Couture, Nadine (Frontiers in Virtual Reality, 2022)
Creativity is key in the early phases of innovation processes. With the rapid evolution of technologies, designers now have access to a large variety of tools to support this activity. Virtual reality (VR) is taking over in multiple domains, especially during conception. But, is VR really facilitating creativity in the initial ideation phases? We compare two sketching modalities through dedicated Creativity Support Tools (CSTs): one in VR and one on a 2D interactive whiteboard. We propose a two-part creativity task (divergent and convergent thinking) to two groups of thirty participants each. We record user experience, creative experience, and creative performance. Our results show that VR is more stimulating, attractive, and engaging. We also observe better level of creativity for the participants using the VR CST. Our results indicate that VR is an effective and relevant tool to boost creativity and that this effect might carry over to following creative tasks.